2010
DOI: 10.1603/ec10087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Four Nematode Species on Fitness Costs of Pink Bollworm Resistance to Bacillus thuringiensis Toxin Cry1Ac

Abstract: Evolution of resistance by pests can reduce the efficacy of transgenic crops that produce insecticidal toxins from the bacterium Bacillus thuringiensis Berliner (Bt). In conjunction with refuges of non-Bt host plants, fitness costs can delay the evolution of resistance. Furthermore, fitness costs often vary with ecological conditions, suggesting that agricultural landscapes can be manipulated to magnify fitness costs and thereby prolong the efficacy of Bt crops. In the current study, we tested the effects of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 58 publications
(87 reference statements)
0
22
0
Order By: Relevance
“…The entomopathogenic nematode Steinernema riobrave Cabanillas, Poinar, and Raulston (Rhabditida: Steinernematidae) has been found to magnify Þtness costs in most experiments (Gassmann et al 2006(Gassmann et al , 2009bHannon et al 2010). Some experimental data also indicated that Heterorhabditis bacteriophora Poinar (Rhabditida: Heterorhabditidae) magniÞed Þtness costs (Gassmann et al 2009b), but in other cases no effects on Þtness costs were detected , Hannon et al 2010. Two additional species of Steinernema and H. sonorensis Stock, Rivera-Orduñ o, and Flores-Lara were evaluated in Hannon et al (2010), but none affected Þtness costs.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The entomopathogenic nematode Steinernema riobrave Cabanillas, Poinar, and Raulston (Rhabditida: Steinernematidae) has been found to magnify Þtness costs in most experiments (Gassmann et al 2006(Gassmann et al , 2009bHannon et al 2010). Some experimental data also indicated that Heterorhabditis bacteriophora Poinar (Rhabditida: Heterorhabditidae) magniÞed Þtness costs (Gassmann et al 2009b), but in other cases no effects on Þtness costs were detected , Hannon et al 2010. Two additional species of Steinernema and H. sonorensis Stock, Rivera-Orduñ o, and Flores-Lara were evaluated in Hannon et al (2010), but none affected Þtness costs.…”
mentioning
confidence: 99%
“…Some experimental data also indicated that Heterorhabditis bacteriophora Poinar (Rhabditida: Heterorhabditidae) magniÞed Þtness costs (Gassmann et al 2009b), but in other cases no effects on Þtness costs were detected , Hannon et al 2010. Two additional species of Steinernema and H. sonorensis Stock, Rivera-Orduñ o, and Flores-Lara were evaluated in Hannon et al (2010), but none affected Þtness costs. Steinernema riobrave has been found to increase Þtness costs for pink bollworm that are homozygous for Bt resistance (i.e., recessive Þtness costs) (Gassmann et al 2006(Gassmann et al .…”
mentioning
confidence: 99%
See 3 more Smart Citations